Social and Solidarity Economy in South American regional governance - Saguier, Marcelo (2017)
The article analyzes the scaling up of the Social and Solidarity Economy (SSE) agenda in the regional integration processes of Union of South American Nations (UNASUR) and MERCOSUR. We ask how the SSE is being used in processes of regional policy cooperation and what implications this has for the construction of regional governance frameworks supportive of social development. Our argument is that the regional processes in the contexts of UNASUR and MERCOSUR adopt a narrow concept of SSE that defines it as a social policy instrument to combat poverty. This limits the transformative potential of the SSE agenda, a more expansionist interpretation of which would otherwise herald the strengthening of socio-productive practices as an alternative to extractivist development in the region.